2020
DOI: 10.3390/toxins12060378
|View full text |Cite
|
Sign up to set email alerts
|

Harmful Algal Bloom Toxicity in Lithobates catesbeiana Tadpoles

Abstract: Harmful algal blooms (HAB) have become a major health concern worldwide, not just to humans that consume and recreate on contaminated waters, but also to the fauna that inhabit the environments surrounding affected areas. HABs contain heterotrophic bacteria, cyanobacterial lipopolysaccharide, and cyanobacterial toxins such as microcystins, that can cause severe toxicity in many aquatic species as well as bioaccumulation within various organs. Thus, the possibility of trophic transference of this toxin through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…In our study, we performed immunostaining of the liver tissues and observed elevated levels of protein carbonylation in the mice that were exposed to the toxin as compared to Vehicle and these levels were lowered upon treatment with targeted antioxidant therapy. Previously we have reported significant increases in protein carbonyl levels in both liver and intestines of tadpoles exposed to 1 µg/L of MC-LR for just 7 days [ 66 ]. In another interesting study conducted by Hwang et al, the authors have reported that repeated MCLR exposure potentiates Kainic Acid-induced excitotoxicity in the hippocampus by enhancing oxidative stress and neuroinflammation through the modulation of p-CaMKII, p-PKC and p-ERK [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we performed immunostaining of the liver tissues and observed elevated levels of protein carbonylation in the mice that were exposed to the toxin as compared to Vehicle and these levels were lowered upon treatment with targeted antioxidant therapy. Previously we have reported significant increases in protein carbonyl levels in both liver and intestines of tadpoles exposed to 1 µg/L of MC-LR for just 7 days [ 66 ]. In another interesting study conducted by Hwang et al, the authors have reported that repeated MCLR exposure potentiates Kainic Acid-induced excitotoxicity in the hippocampus by enhancing oxidative stress and neuroinflammation through the modulation of p-CaMKII, p-PKC and p-ERK [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia has been shown to cause serious abnormalities in the central nervous system of bullfrog (Lithobates catesbeianus) larvae, and reduce body mass and length in exposed individuals [95]. Extreme temperatures also increase bacterial blooms in ponds, giving rise to deleterious pathogens, such as heterotrophic bacteria (Cyanobacterial lipopolysaccharide) and cyanobacterial toxins (microcystins) that can affect embryo masses and cause significant liver and intestinal toxicity in larvae [90,96]. Such changes in temperature can also compromise immunity at the larvae stage, leading to increased susceptibility to infections [97,98].…”
Section: Climate Changementioning
confidence: 99%
“…MCs’ impact on the gut is not confined to mammalian species. In another study done in Lithobates catesbeiana (American bullfrog) tadpoles, it was observed that acute, short-term exposure of tadpoles to HAB toxins containing 1 μg/L (1 nmol/L) of total microcystins for only 7 days resulted in significant liver and GI toxicity [ 86 ]. MC-LR-exposed tadpoles showed increased intestinal diameter, decreased intestinal fold heights, and a constant number of intestinal folds, indicating pathological intestinal distension, similar to toxic megacolon.…”
Section: Microcystins and Gut Healthmentioning
confidence: 99%
“…These findings underscore the need to evaluate the GI-related effects related to HAB toxin exposure, including MCs. This also highlights the need to evaluate the influence HAB toxins may have on other vulnerable species within the food web and how those may ultimately also impact human health [ 86 ].…”
Section: Microcystins and Gut Healthmentioning
confidence: 99%